Wiretapping Gaps Threaten Presumption of Innocence in New Criminal Procedure: Kekosongan Aturan Penyadapan Mengancam Asas Praduga Tak Bersalah - Putri, Naura Atha Fadhila Salvia Berti; Rusdiana, Emmilia (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Criminal procedure must reconcile effective law enforcement with legality, due process, privacy, and the presumption of innocence. Specific Background The new Criminal Procedure Code recognizes wiretapping as a coercive measure and grants investigators authority to use it in criminal investigation, while its detailed procedures remain delegated to a separate statute. Knowledge Gap Existing discussions on coercive measures have largely centered on arrest, detention, search, seizure, and pretrial oversight, whereas wiretapping under the new procedural regime remains insufficiently examined, particularly in relation to the presumption of innocence and the absence of comprehensive procedural safeguards. Aims This study analyzes the authority to conduct wiretapping as a coercive measure and its legal implications for privacy rights, legality, due process of law, and the presumption of innocence. Results The findings show that wiretapping is relevant for uncovering modern crimes involving technological communication, but the lack of clear rules on implementation, judicial authorization, supervision, subject limits, offense categories, duration, and accountability creates legal uncertainty and opens space for abuse of authority. Wiretapping at the preliminary stage may also place individuals who have not been named suspects under state surveillance, thereby risking privacy violations and weakening the presumption of innocence. Novelty The study positions wiretapping as a high-intrusion coercive measure that requires strict subsidiarity, proportionality, and judicial control before use. Implications Comprehensive regulation is needed to balance criminal law enforcement with human rights protection and to secure the validity of electronic evidence in criminal justice. Highlights • Coercive interception supports the detection of technology-based crime.• Procedural uncertainty opens room for misuse of investigative authority.• Judicial control is needed to balance enforcement and human rights. Keywords Wiretapping; Coercive Measures; Presumption Of Innocence; Criminal Procedure; Human Rights